The Effects of Macroeconomic Indicators on Leveraged Forex Volume: Evidence from Turkey - Tuncay Turan Taraboğlu; Tuğba Nur Topaloğlu; Serdar Yaman (Istanbul Business Research (IBR), 2019)
In this study, the effects of macroeconomic indicators on leveraged forex volumes of financial intermediary institutions have been analyzed. The study covers the data for the period 2013Q1-2017Q2 of 16 financial intermediary institutions operating in Turkey. In the study in regards to macroeconomic indicators, BIST 100 Index revenues (BIST), consumer price index (CPI), consumer confidence index (CCI), average rate applied to deposits opened by banks (INT), gold prices (GOLD), money supply (M2), external trade export unit index (EUVI) and unemployment rate (UNEMP) have been used. In the study, the effects of macroeconomic indicators on leveraged forex volume have been examined through panel data analysis. As a result of the panel data analysis, it has been determined that the BIST, M2, EUVI and UNEMP variables have positive significant effects on leveraged forex volume and that the INT variable has negative significant effects on leveraged forex volume. In the study, the effects of CPI, CCI and GOLD variables on leveraged forex volume are statistically insignificant.
Keywords: 650; Forex market; Leveraged forex volume; Macroeconomic indicators; Panel data analysis